Non-linear matrix completion. (May 2018) - Fan, Jicong; Chow, Tommy W.S.
Highlights: Conventional matrix completion methods are linear methods. This paper proposed a non-linear matrix completion (NLMC) method that is able to handle data of non-linear structures and high-rank matrices. NLMC significantly outperforms existing methods in the tasks of image inpainting and single-/multi-label classification. The idea of NLMC is extended to a non-linear rank-minimization framework applicable to other problems such as non-linear denoising. Abstract: Conventional matrix completion methods are generally linear because they assume that the given data are from linear transformations of lower-dimensional latent subspace and the matrix is of low-rank. Therefore, these methods are not effective in recovering incomplete matrices when the data are from non-linear transformations of lower-dimensional latent subspace. Matrices consisting of such nonlinear data are always of high-rank or even full-rank. In this paper, a novel method, called non-linear matrix completion (NLMC), is proposed to recover missing entries of data matrices with non-linear structures. NLMC minimizes the rank (approximated by Schatten p -norm) of a matrix in the feature space given by a non-linear mapping of the data (input) space, where kernel trick is used to avoid carrying out the unknown non-linear mapping explicitly. The proposed NLMC is compared with existing methods on a toy example of matrix completion and real problems including image inpainting and single-/multi-label classification. The experimental results verify the effectiveness and superiority of the proposed method. In addition, the idea of NLMC can be extended to a non-linear rank-minimization framework applicable to other problems such as non-linear denoising.